Real Time Piano Finger Recognition Using Convolutional Neural Networks and Gated Recurrent Units (Informatica, 2025)
Standardized piano fingering practice not only concerns the stability of performance, but also directly affects the richness and coherence of musical expression. However, due to limitations in teacher resources and teaching time, existing piano teaching has significant shortcomings in personalized guidance and immediate feedback on errors. Therefore, this article proposes a computer vision based piano finger recognition and training system, which integrates convolutional neural networks (CNN) for hand static feature extraction, gated recurrent units (GRU) for action time series modeling, and introduces spatial attention and temporal attention mechanisms to improve finger recognition accuracy and dynamic response capability. The experiment was conducted based on a self built dataset of over 130000 piano performance images. The system outperformed existing methods in key indicators such as finger gesture recognition accuracy (89.8%), macro average F1 value (90.2%), and feedback response delay (0.47 seconds), especially in complex action recognition and real time feedback. The research results provide feasible technical support for the piano intelligent teaching system and have good application and promotion value.